2007
DOI: 10.1164/rccm.200606-769oc
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics Applied to Exhaled Breath Condensate in Childhood Asthma

Abstract: Metabolomics can be applied to exhaled breath condensate, leading to the characterization of airway biochemical fingerprints. The presence of acetylated compounds suggests new metabolic pathways that may have a role in asthma pathophysiology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
189
1
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 217 publications
(199 citation statements)
references
References 29 publications
6
189
1
3
Order By: Relevance
“…Although NMR has a lower sensitivity compared to enzyme-linked immunosorbent assay (ELISA) and mass spectrometry, it is a non-destructive analytical method that requires minimal sample preparation and has rapid acquisition time of about 10 -15 min [ 104 ]. NMR-based metabolomics of EBC may have a potential use in characterising respiratory diseases as it was able to discriminate patients with COPD [ 104 ], asthma [ 106 ], stable and unstable cystic fibrosis [ 107 ] from healthy subjects. In addition, a recent NMR spectroscopic study has also shown that the repeated use of the EcoScreen ® condenser does not cause any carry-over effect and the disinfectant Milton does not alter EBC metabolomics [ 100 ], as opposed to another study that reported artificial signals when the Anacon condenser was used and disinfected with Descogen [ 108 ].…”
Section: Nmr Spectroscopy-based Metabolomicsmentioning
confidence: 99%
“…Although NMR has a lower sensitivity compared to enzyme-linked immunosorbent assay (ELISA) and mass spectrometry, it is a non-destructive analytical method that requires minimal sample preparation and has rapid acquisition time of about 10 -15 min [ 104 ]. NMR-based metabolomics of EBC may have a potential use in characterising respiratory diseases as it was able to discriminate patients with COPD [ 104 ], asthma [ 106 ], stable and unstable cystic fibrosis [ 107 ] from healthy subjects. In addition, a recent NMR spectroscopic study has also shown that the repeated use of the EcoScreen ® condenser does not cause any carry-over effect and the disinfectant Milton does not alter EBC metabolomics [ 100 ], as opposed to another study that reported artificial signals when the Anacon condenser was used and disinfected with Descogen [ 108 ].…”
Section: Nmr Spectroscopy-based Metabolomicsmentioning
confidence: 99%
“…Carraro et al [10] first applied NMR-based metabolomics to EBC of asthmatic children, who were distinguished from healthy controls by the variation of the acetate signal. The authors speculated that such enhancement was due to an increased acetylation of proinflammatory proteins in the extracellular space of the airway environment.…”
Section: Phenotyping Ebcmentioning
confidence: 99%
“…Model derived features were selected as those with a VIP score >= 1.0. PLSDA is commonly used in metabolomics investigations including multiple forms of cancer, cardiac ischemia, parkinson's disease and asthma (Nishiumi et al, 2010;Bodi et al, 2012;Bogdanov et al, 2008;Carraro et al, 2007;Chen et al, 2011;Duarte et al, 2010;Qiu et al, 2010). This technique has also been previously implemented in our lab investigating hemorrhagic shock (Lexcen, Lusczek, Witowski, Mulier, & Beilman, 2012).…”
Section: Partial Least Squares Discriminant Analysis (Plsda)mentioning
confidence: 99%